Countering extremism building social resilience through community engagement - Gunaratna, Rohan; Jerard, Jolene; Nasir, Salim Mohamed (Imperial College Press insurgency and terrorism series, 2013)
This unique work is the first to address the subject of community engagement strategies in countering extremism, and explores the development and research of these strategies.